Contextualization Of Short Story Patterns In Indonesian Texbooks For Class IX SMP - Pesta Kristina Manik (CV. AFDIFAL MAJU BERKAH, 2022)
Literary works of prose fiction has two main elements, i.e. the elements of the intrinsic and extrinsic elements. The elements of the intrinsic is the most important element to support the passage of the story. Extrinsic elements are outside elements that help build and support a story that is the background of the author of the story and the social conditions of a culture. The purpose of this research is to know is in the pattern of the elements contained in a short story in the book text Bahasa Indonesia kelas IX SMP. This study uses a qualitative method for solving the problem are investigated to describe or write down the circumstances in each story. The source of the data used for this study using the book text Book of Indonesian Language and Literature SMP/MTS class IX Revised Edition 2013 curriculum written by Endah Tri Priyanti-M. Thamrin - Hadi Widodo. The Publisher Of The Earth Script. Book Bahasa Indonesia (Electronic School Book) for SMP/MTS written by Atikah Anindryani-Yuwono-Suhartono, published in 2018. Book Bahasa Indonesia SMP/MTS class IX the Ministry of Education And Culture Republic of Indonesia Revised 2018. Book Language Independent Indonesia SMP/MTS Erlangga Publisher, written by Engkos Kosasish-Restudi, Curriculum revision 2013. The results of the analysis of contextual pattern of short stories in the book text Bahasa Indonesia kelas IX SMP includes elements, characters/characterizations, plot,setting, point of view, the mandate and the style of the language. The value of a character in a short story Bahasa Indonesia kelas IX SMP namely, curiosity, Responsibility, Friendly, Creative, Peace-loving, Religious, patriotism, Discipline, Social Care, Democratic Values, tolerance,hard Work,Social Care